Giant pulmonary bulla causing respiratory compromise in a very low‐birthweight infant. Issue 11 (15th November 2022) - Shinohara, Tamao; Hasebe, Yohei; Watanabe, Daisuke; Sakurayama, Tomohide; Maebayashi, Yuki; Numano, Fuminori; Saito, Tomohiro; Koizumi, Keiichi; Nemoto, Atsushi; Saito, Akitoshi; Oyama, Toshio; Oyachi, Noboru; et al.
Abstract: Acquired cystic lung disease in premature infants is a serious respiratory complication, and pulmonary interstitial emphysema (PIE) has been widely reported. We report a rare case of giant pulmonary bulla in an infant treated with bullectomy where chest computed tomography was useful in directing treatment. Abstract : Acquired cystic lung disease in premature infants is a serious respiratory complication, and pulmonary interstitial emphysema (PIE) has been widely reported. We report a rare case of giant pulmonary bulla in an infant treated with bullectomy where chest computed tomography was useful in directing treatment.